Respuestas

2013-11-27T12:29:25+01:00

Función afin
                          y = b + ax
                                b = ordenada en el origen
                                a = pendiente
                                         a = (y2 - y1)/(x2 - x1)
Del enunciado:
                             a = (- 4 - 4) / (- 6 - 3)
                                = - 8/- 9
                             a = 8/9
y = b + 8/9x
En P(3,4)
                     4 = b + 8/9(3)
                      b = 4 - 8/3
                         = 12/3 - 8/3
                     b = 4/3
                                                                y = 4/3 + (8/9)x